2022
DOI: 10.13057/biodiv/d230861
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Sunda porcupine quill extract (Hystrix javanica) against Staphylococcus aureus

Abstract: Abstract. Gifardi MD, Sutardi LN, Farida WR, Prawira AY, Agungpriyono S. 2022. Antibacterial activity of Sunda porcupine quill extract (Hystrix javanica) against Staphylococcus aureus. Biodiversitas 23: 4355-4360. The Sunda porcupine (Hystrix Javanica) is a rare mammal with quill-like hair covering its body. Because the Sunda porcupine has extensive sebaceous glands, the neutral carbohydrate content is well-distributed and is known to have excellent wound healing. In addition, the high acid content of porcupin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…These active ingredients serve as antioxidant, wound healer, analgesic, antibacterial, anti-inflammatory, antiviral, antioxidant, antifungal, and immunomodulator [18,19,20,21]. In addition, research by Gifardi et al [13] demonstrated that the nhexane extract of porcupine quills exhibits potent antibacterial activity against S. aureus. When compared to the commercial products tested in this study, which contain antibiotic ingredients, the antibiotic function of porcupine quill extract is able to suppress bacterial growth in the wound area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These active ingredients serve as antioxidant, wound healer, analgesic, antibacterial, anti-inflammatory, antiviral, antioxidant, antifungal, and immunomodulator [18,19,20,21]. In addition, research by Gifardi et al [13] demonstrated that the nhexane extract of porcupine quills exhibits potent antibacterial activity against S. aureus. When compared to the commercial products tested in this study, which contain antibiotic ingredients, the antibiotic function of porcupine quill extract is able to suppress bacterial growth in the wound area.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Gene ontology analysis, 3 proteins in porcupine quills have antibacterial and wound healing roles, namely keratin, type II cytoskeletal 1 (KRT1); keratin, type II cytoskeletal 6A (Krt6a); annexin (ANXA2) [12]. Porcupine quills fat extract using n-Hexane solvent is known to have antibacterial activity against Staphylococcus aureus which is included in the strong category at a concentration of 25%-100% [13]. In addition, research conducted by Budiman et al [14] conducted research which showed that the ethanolic extract of porcupine quills is composed of several bioactive compounds such as alkaloids, flavonoids, saponins, triterpenoids, steroids and peptides.…”
Section: Introductionmentioning
confidence: 99%